Fabrication of provisional restoration on freshly prepared tooth: indirect and direct technique (Bangladesh Journal of Medical Science, 2015)
Background: Provisional restorations are fabricated to protect the prepared tooth structure during period between the preparation and the final restoration, and the techniques applied are direct, indirect and indirect direct. Various materials are used to fabricate provisional restoration, such as, preformed crown, acrylic, metal shell, composite, etc. Objectives: The study was designed to evaluate the advantages of fabrication of provisional restorations by indirect technique over direct technique. Methods: This prospective comparative study carried out in the Department of Prosthodontics, Faculty of Dentistry, Bangabandhu Sheikh Mujib Medical University, Dhaka, from January 2006 to December 2007, included 20 patients each for insertion of provisional restorations fabricated by indirect (group A) and direct (group B) technique. Outcome was evaluated on the basis of marginal adaptation, biocompatibility and aesthetic status. Results: On day 7 of provisional restoration, grade I marginal adaptation were observed in 75% and 40% of group A and group B patients, respectively, and on day 15 were 75% and 20%, respectively. Grade I biocompatibility on day 7 of group A patients were 100% and group B 30%, and on day 15 was 95% and 35%, respectively. Grade I aesthetic status on day 7 were in 100% of both group A and group B patients, and on day 15 was 95% and 85%, respectively. None of the patients was in grade III, either in marginal adaptation, biocompatibility or aesthetic status. Conclusion: Indirect provisional restoration is better and safer in relation to marginal adaptation, biocompatibility and aesthetic status.DOI: http://dx.doi.org/10.3329/bjms.v14i1.21560 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.59-64